Przedmiot prawa autorskiego. Przypadki graniczne - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
This study attempts to determine borderline between works and products which are not protected by copyright law on account of thesufficient degree of creativity involved. The legal definition is stipulated by Art. 1 of the Act on Copyright and Related Rights of February 4, 1994, but it does not provide a definitivefferentiation in certain borderline cases, that is whenever a low level of creativity raises substantial doubts as ther to include a given category in a group of works.